2018
DOI: 10.1123/jmld.2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Relationship Between Adolescents’ Perceived and Actual Fundamental Movement Skills and Physical Activity

Abstract: Objectives: To explore the relationship between fundamental movement skill (FMS) competence, perceived FMS competence and physical activity (PA) in adolescents. Methods:The Test of Gross Motor Development (TGMD), the TGMD-2 and the Victorian Skills manual were used to assess FMS competence (locomotor, object control and stability).The Physical Self Confidence scale was used to assess perceived FMS competence (locomotor, object control and stability). Moderate to vigorous intensity PA (MVPA) was measured via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
2
7
0
3
Order By: Relevance
“…In accordance with previous literature, there were significant sex-differences in perceived MC between males and females [38,39,40,41] as males’ perceived MC was significantly higher than that of females. Prior studies have tended to report that males perceive themselves more proficient in MC than females [38,39,40,41]. This current study suggests that this is the case in British early years children, and whilst not a novel finding in the literature, it has not previously been established in British early years children.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous literature, there were significant sex-differences in perceived MC between males and females [38,39,40,41] as males’ perceived MC was significantly higher than that of females. Prior studies have tended to report that males perceive themselves more proficient in MC than females [38,39,40,41]. This current study suggests that this is the case in British early years children, and whilst not a novel finding in the literature, it has not previously been established in British early years children.…”
Section: Discussionsupporting
confidence: 91%
“…This study’s findings as well as those of previous Irish [ 22 , 57 , 87 ] and international work [ 34 , 43 , 88 ] suggest that high PMC values are common in later childhood and early adolescence. Furthermore, these values may even remain stable with aging; a study of Dutch and German children ( n = 198; male = 110; female = 88; mean age = 9.35 ± 0.67 years) found no significant differences in their perception of ability a year after their initial assessment, with values still remaining high [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…This potentially indicates that the theoretical assumption of greater accuracy of assessing one’s PMC as children age may be flawed. The reasons for this are innumerable; it has been suggested that enhanced awareness and social comparisons of their peers may interfere with self-assessment among adolescents [ 87 ]. The potential for social desirability bias impacting on self-report data should be noted; this is a common problem in PA research, where a disconnect between reported behavior and actual behavior exists [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…La revisión bibliográfica realizada, muestra que los datos de esta investigación, respecto a la competencia motriz de chicos y chicas, concuerdan con resultados de anteriores investigaciones, en las que se observa que los chicos, presentan un nivel más alto de competencia motriz, que las chicas (Gómez et al, 2006;Ruiz, 2010;Katic et al, 2013;Lorson et al 2013;McGrane, Powell, Belton, & Issartel, 2018;Ruiz & Graupera, 2003;Shibley, 2005).…”
Section: Discussionunclassified